(untitled) (Journal of Science and Technology, 2016)
Good uniform thin films of cobalt sulphide ((u) were successful& deposited on glass slides by improved solution growth technique (Minot 300K for 24 hours. and at pH of 7 - 12. The effect, of deposition bath pH and constitutions were studied Optical properties of the deposited thin films were dependent on the pH values. Average values of optical properties include transmittance (I) front 11.122 to 0.199. refinance (R) from 0.055 to 0.093, coefficient of absorption (a) from 0.106 t 10P to 0.196 X 104 cm’ and refractive index (n) from 1,61 to 1.84 The solid state properties include handgun E.g. from 2.12 to 2.66 el: electrical conductivity (0) from 0.90 x 10’ to 1.53 N 10 ’ (ohm -cm)’ and film thickness It) from 383 to 487.A. flinty with refractive index (n) lower than 1.8 have high transmittance (I) and low reflectance (R) characteristic. Those with refractive index (n) greater than 1.8 have low transmittance (1) and high reflectance Oil properties. Possible applications of the deposited thin films were discussed